2017
DOI: 10.1590/1980-57642016dn11-010009
|View full text |Cite
|
Sign up to set email alerts
|

Performance on cognitive tests, instrumental activities of daily living and depressive symptoms of a community-based sample of elderly adults in Rio de Janeiro, Brazil

Abstract: ObjectiveTo describe the performance on basic cognitive tasks, instrumental activities of daily living, and depressive symptoms of a community-based sample of elderly adults in Rio de Janeiro (Brazil) who participated in multiple physical, social, and cognitive activities at government-run community centers.MethodsA total of 264 educated older adults (> 60 years of age of both genders) were evaluated by the Brief Cognitive Screening Battery (BCSB), Lawton's and Pfeffer's activities of daily living indexes, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
(98 reference statements)
0
5
0
1
Order By: Relevance
“…Table 3 shows the performance in FMT stratified by education. 31 These studies demonstrate that the scores in DR-FMT of the BCSB suffer little or no effect from may vary according to the presence or absence of cognitive impairment.…”
Section: Influence Of Education Construct Validity and Normative Studiesmentioning
confidence: 75%
See 2 more Smart Citations
“…Table 3 shows the performance in FMT stratified by education. 31 These studies demonstrate that the scores in DR-FMT of the BCSB suffer little or no effect from may vary according to the presence or absence of cognitive impairment.…”
Section: Influence Of Education Construct Validity and Normative Studiesmentioning
confidence: 75%
“…However, when the performance of individuals in these education levels was compared to that of individuals with ≥10 years of schooling, there was a modest but significant difference (p<0.05). 26 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No entanto, esse declínio pode influenciar na autonomia e autocuidado do isso, assim como na realização de suas atividades cotidianas, repercutindo significativamente em sua qualidade de vida. Além disso, variáveis sociodemográficas como escolaridade, idade, sexo, perfil socioeconômico e estado civil influenciam no perfil cognitivo do idoso (Lima et al, 2017).…”
Section: Introductionunclassified
“…It has a high incidence in the elderly people and can be considered a risk factor for the development of dementia. [1][2][3][4][5] A meta-analysis showed that depression in patients with mild cognitive impairment is 32%, and cognitive deficits were found more often in elderly depressed people than in younger depressed adults. 6,7 In contrast, semantic memory deficits of 12 years before diagnosing Alzheimer's disease were established.…”
Section: Introductionmentioning
confidence: 99%